DAMPAK KEBIJAKAN PEMEKARAN WILAYAH: STUDI KASUS DI DESA PRINGGASELA KECAMATAN PRINGGASELA LOMBOK TIMUR - M. Adib Zata Ilmam; Lalu Moh. Nazar Fajri; Hamdi, Hamdi; Muh. Syamsurriadi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The division of territory by the South Pringgasela Village Government is aimed at enhancing Village Governance. This study analyzes the impacts of hamlet division on the progress of Village Governance, as well as the supporting and hindering factors in South Pringgasela Village, East Lombok Regency. A qualitative descriptive method was employed, with the research conducted in South Pringgasela Village. Primary data was collected through interviews, while secondary data consisted of documentation and observations. The results reveal both positive and negative impacts of hamlet division. Positive impacts include improvements in governance efficiency, social order, and well-organized territorial management. Negative impacts involve community apprehension, limited involvement, and communication breakdown. Supporting factors encompass territorial size, population numbers, and community aspirations, while hindering factors include the complexity of the division process and social obstacles. Recommendations involve active community participation in Village Governance and clear regulations in village bylaws. Understanding the impacts and related factors of hamlet division is expected to support more effective and sustainable planning and implementation of division policies.